Evaluation of Geenius HIV-1/2 Confirmatory Assay for the confirmatory and differential diagnosis of HIV-1/HIV-2 in Japan and reliability of the Geenius Reader in the diagnosis of HIV-2 - Kusagawa, Shigeru; Kawana-Tachikawa, Ai; Matsubayashi, Keiji; Hoshi, Yuji; Ishimaru, Ken; Hamaguchi, Isao (BMC infectious diseases, 2021)
NEW LAV BLOT I and II (LAV I and LAV II), they were only option for human immunodeficiency virus (HIV) confirmatory test, following HIV screening test using HIV Ag/Ab combination test in Japan. We evaluated the performance of Geenius HIV-1/2 Confirmatory Assay (Geenius), both as a confirmatory test and for differentiation between HIV-1 and HIV-2, in comparison with LAV I and LAV II. Eighty-nine HIV-1-positive plasma specimens, one anti-HIV-1 low-titer performance panel, 10 seroconversion panels, and two anti-HIV-1/2 combo performance panels were tested. The results were read with the Geenius Reader and by visual reading. All 89 HIV-1-positive plasma specimens were identified as HIV-1-positive using Geenius; this 100% success rate was superior to that with LAV I (95.5% using WHO criteria, 98.9% using CDC criteria). The HIV-1-positive specimens showed low cross-reactivity with HIV-2 lines in Geenius. The sensitivity of Geenius for HIV-1 detection was the same as or greater than that of LAV I, but less than that of Genscreen HIV Ag-Ab ULT, in our analysis of the commercial performance and seroconversion panels. In contrast, five of the 13 HIV-2-positive specimens that had been identified as HIV-positive untypable by visual reading because of their cross-reactivity to HIV-1 lines were successfully identified by the Geenius Reader as HIV-2-positive with cross-reactivity. Geenius provides strong performance for HIV confirmatory tests and HIV-1 differentiation tests. However, when visual reading is used, its performance in HIV-2 differentiation is less reliable. Because HIV-2 infection has been sporadically reported in Japan, the use of the Geenius Reader is preferable to ensure more reliable HIV-1/HIV-2 differentiation.